Analysis of the distribution of wealth in Ireland - Chesher, Andrew (Economic & Social Studies, 1979)
Lyons' (1972) data on the distribution of Irish wealth are considered and the appropriateness of the lognormal and Pareto models for this data are assessed using relatively sophisticated statistical methods. Allowance is made for the 65 per cent of individuals whose estate size is unrecorded. New estimates of total wealth and of the distribution of wealth in Ireland are obtained. Part of the analysis reported here can be regarded as formalising the procedure adopted by Chesher and McMahon (1977) when considering the same data. The lognormal distribution performs surprisingly well, but the Pareto distribution provides a poor model for the Irish data.
Keywords: Wealth Distribution; Ireland